(untitled) (Journal of Computational Mathematics, 1996)
A procedure of computing the position of the planar Stewart platform with coplanar ground points is presented avoiding the computation of Groebner basis by standard algorithm. The polynomial system resulted is triangularized. The number of arithmetic operations needed can be precisely counted.